Wildfire effects on BVOC emissions from boreal forest floor on permafrost soil in Siberia - Zhang-Turpeinen, Huizhong; Kivimäenpää, Minna; Aaltonen, Heidi; Berninger, Frank; Köster, Egle; Köster, Kajar; Menyailo, Oleg; Prokushkin, Anatoly; Pumpanen, Jukka (Science of The Total Environment, 2022)
One of the effects of climate change on boreal forest will be more frequent forest wildfires and permafrost thawing. These will increase the availability of soil organic matter (SOM) for microorganisms, change the ground vegetation composition and ultimately affect the emissions of biogenic volatile organic compounds (BVOCs), which impact atmospheric chemistry and climate. BVOC emissions from boreal forest floor have been little characterized in southern boreal region, and even less so in permafrost soil, which underlies most of the northern boreal region. Here, we report the long-term effects of wildfire on forest floor BVOC emission rates along a wildfire chronosequence in a Larix gmelinii forest in central Siberia. We determined forest floor BVOC emissions from forests exposed to wildfire 1, 23 and > 100 years ago. We studied how forest wildfires and the subsequent succession of ground vegetation, as well as changes in the availability of SOM along with the deepened and recovered active layer, influence BVOC emission rates. The forest floor acted as source of a large number of BVOCs in all forest age classes. Monoterpenes were the most abundant BVOC group in all age classes. The total BVOC emission rates measured from the 23- and >100-year-old areas were ca. 2.6 times higher than the emissions from the 1-year-old area. Lower emissions were related to a decrease in plant coverage and microbial decomposition of SOM after wildfire. Our results showed that forest wildfires play an important indirect role in regulating the amount and composition of BVOC emissions from post-fire originated boreal forest floor. This could have a substantial effect on BVOC emissions if the frequency of forest wildfires increases in the future as a result of climate warming. (C) 2019 Elsevier B.V. All rights reserved. Peer reviewed